The personal authentication service and security enhancement for optimal strong password. (29th November 2018) - ShanmugaPriya, S.; Valarmathi, A.; Yuvaraj, D.
Summary: The ability of the Cloud to share information and provide certain services to the network linked people. The resources are provided according to the need of the user. In cloud, the user's data are moved to the large data storage, which must be secured. The various organization have expressed concerns about security aspects of cloud computing. One of the major perspectives is to provide security to one's data, which is stored remotely from the user's location. This paper describes an enhanced approach for the already used data security model in cloud environment. The proposed data security model includes generation of OTP using HMAC (Hash based message authentication code) for user authentication process. This paper also includes a comparative MD5 and SHA algorithms for the better implementation of the model. This model best suits for any of the layers in it, to achieve this we use certain encryption algorithms that convert original text to the form that is not understood by the third party. Finally, data availability can be considered as a major concern, which is viewed as threat associated with the cloud environment. To overcome this problem, we generally replicate our data and store it in various locations.